Occurrence of the genus Eustrongylides sp. Parasite (Nematoda: Dioctophymatidae) in Chrisichthys macropogon and Synodontis clarias from Lower River Benue - S., OMEJI,; J.O., JIMOH,; A.A, GARBA, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Occurrence of parasites of the genus Eustrongylides sp. (Nematoda: Dioctophymatidae) in Chrisichthys macropogon and Synodontis clarias from Lower River Benue in Makurdi, Benue State, Nigeria was investigated. Of the 50 S. clarias, 28.00% were infested with 113 Eustrongylides sp., while the stomach accounted for 20.35% of the parasite load, intestine had 79.64%. 56.00% parasite prevalence and 0.56 parasite intensity were recorded for S. clarias. In addition, of the 50 C. macropogon, 21.00% were infested with 57 Eustrongylides sp., while the stomach accounted for 22.81% of the parasite load, intestine had 77.19%. 42.00% parasite prevalence and 0.42 intensity were recorded for C. macropogon, respectively. Variation in percentage parasite infestation between male and female S. clarias and C. macropogon existed, being more in female S. clarias (60.18%) than the male (39.82%). On the contrary, percentage parasite infestation was more prevalent in male C. macropogon (64.91%) than the female (35.09%).